Trade Remedies And Non-Market Economies : Economic Implications of The First US Countervailing Duty Case On China - Zhao, Longyue (The World Bank, 2008)
In 2007, the United States Department of Commerce altered a 23-year old policy of not applying the countervailing duty law to non-market economies, and initiated eight countervailing and antidumping duty investigations on Chinese imports. The change brings heated debate on trade remedy policies and issues of non-market economies. This study focuses on the first countervailing duty case on imported coated free sheet paper from China and analyzes the implications of this test case for United States-China bilateral trade, and industrial policies in transitioning market economies. The paper also provides a brief review of the economics of subsidies, World Trade Organization rules on subsides and countervailing measures, and United States countervailing duty laws applied to non-market economies. While recently acceded countries should review their domestic development policies from the perspective of economic efficiency and comply with the World Trade Organization rules, it is also important to further clarify the issues of non-market economies under the multilateral trading system, and pay keen attention to the rules negotiations in the current World Trade Organization Doha Development Round